Implicit definition as unifying logic of mental representation - Kuyumcuoğlu Tütüncüoğlu, Nezihe Müge. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2023., 2023)
The problem of intentional nature of mental representations remains a priority in analytic philosophy and cognitive science. Its impact on the foundations of logical and ontological statements, such as variable referencing over objects, reveals its fundamental importance. The prevalent notion of mental representation, influenced by external representation, treats representations as static stand-ins. This poses challenges in accounting for dynamic aspects such as mensurable change and unity of representations, misrepresentation, and errors detectable by agents. Understanding mental representations therefore has implications for our best understanding of knowledge and learning. This thesis investigates the interactivist notion of mental representation, modeled after implicit defining, as an alternative. In this view, mental representations do not strictly correspond to their contents but rather "define" them, analogous to how axiomatic systems define their terms. The concept of implicit representing sheds light on the contentful nature of habits as a foundational mode of interaction. The interactivist alternative is explored with a view towards the historical development of analytic philosophy, elucidating the relationship between implicit defining, the logical operation, and the ontology of mental representation. It explicates key concepts such as habit, diagrammatical reasoning, abstraction vs. exemplification, problem of induction, functionalism, inferential role semantics, interventionist theory of causation, measure theory, concepts versus properties, framing, systematicity, and productivity. The thesis traces the reactions of analytic philosophy against pragmatism, offering a fully functionalist, operation-based, and pragmatist perspective that abandons structural notions. It shifts the core of explanation from linear mechanistic models to emergentist models of constraints and an interventionist account of causality.
Keywords: Mental representation.